Antibacterial property of membrane processed moringa oleifera seed extract - Idris Oseni, Munirat; Muyibi, Suleyman Aremu; Abdul Karim, Mohamed Ismail; Jamal, Parveen; Mohd. Salleh, Hamzah; Jami, Mohammed Saedi (2013)
The importance of water disinfection is clear and undoubtedly acknowledged; concerns have also been raised over safety issues especially with the use of chlorine. Moringa oleifera seed extracts has been found to possesses antibacterial properties, which can be harnessed as disinfectant for drinking water purposes. In this research, the antibacterial property of the membrane processed seed extract was investigated against Escherichia coli, Pseudosomonas aeruginosa Bacillus subtilis and Staphylococcus aureus. The seeds were prepared with water and salt solution after the seed oil was removed and the extracts obtained were passed through 0.45μm microfiltration membrane system. The antibacterial activity was determined using the agar well diffusion method. The effect of various concentration of the membrane processed seed extract was done, the Minimum Inhibitory Concentration (MIC) as well as Minimum Bactericidal Concentration (MBC) was also carried out for the membrane processed seed extract. The MIC values of membrane processed water extract obtained were 0.78 mg/ml, 1.562 mg/ml, 3.125 mg/ml, and 3.125 mg/ml for Escherichia coli, Pseudosomonas aeruginosa, Bacillus subtilis, and Staphylococcus aureus respectively. The MIC values obtained for salt solution extract are 0.78 mg/ml, 1.56 mg/ml, 3.125 mg/ml, and 3.125 mg/ml for Escherichia coli, Pseudosomonas aeruginosa, Bacillus subtilis, and Staphylococcus aureus respectively. The results showed that membrane processed seed extract possess antibacterial activity that can be harnessed as disinfectant in water.